Enhancing corrosion resistance of zinc-filled protective coatings using conductive polymers - Kohl, Miroslav; Kalendová, Andréa; Schmidová, Eva (Springer, 2017)
Organic coatings containing zinc are amply used for the protection of metals, particularly steel structures. Ways to reduce the zinc content in the coating materials are sought for environmental and financial reasons. Our previous work (Kohl, Prog Org Coat 77:512-517, 2014; Kohl and Kalendova, Mater Sci Forum 818: 171-174, 2015a) suggested that one of the options consists in the use of conductive polymers in the formulation of the zinc coatings. The benefits of conductive polymers include non-toxicity, high stability, electric conductivity and redox potential. Previously we focussed on the effect of conductive polymers added to the organic coatings so as to complete the zinc volume concentration to 67%. The anticorrosion efficiency of the organic coatings was found to improve with increasing polyaniline phosphate or polypyrrole concentrations. Zinc content reduction in the system, however, did not attain more than 5%. The present work focusses on systems where the organic coatings are prepared with zinc having a pigment volume concentration PVC = 50%. Zinc content reduction in the system attains up to 20%. This work examines the mechanical and anticorrosion properties of the organic coatings with reduced zinc contents. The present work was devoted to the feasibility of using of conductive polymers in the formulation of coatings with reduced zinc contents. The conductive polymers included polyaniline, polypyrrole and poly(phenylenediamine); these were synthesised and characterised using physico-chemical methods. Polyphenylenediamine as a potential corrosion inhibitor has not been paid adequate attention so far. Subsequently, organic coatings with reduced zinc contents and containing the pigments at 0.5, 1 and 3% volume concentrations were formulated. The coatings were subjected to mechanical tests and accelerated corrosion tests to assess their mechanical and corrosion resistance.
Zvýšení korozní odolnosti zinkem plněných ochranných povlaků pomocí vodivých polymerů.
Keywords: Coating; Corrosion; Conductive polymers; Zinc; Povlak; koroze; vodivé polymery; zinek